2018
DOI: 10.18311/jbc/2018/17931
|View full text |Cite
|
Sign up to set email alerts
|

Habitat diversification in the cultivation of Indian sandalwood (Santalum album Linn.): An ideal option to conserve biodiversity and manage insect pests

Abstract: In 15 combinations of growing sandalwood with other plant species the incidence of insect pests and their predators were observed for two years from 2014 to 2015 in Karnataka. The more diversified areas recorded more species of insect pests and natural enemies but the severity of the infestations were less and resulted in no insecticidal application. In less diversified areas the severity of sap suckers and stem borers were more often seen and resulted in undertaking control measures. An analysis of sapsuckers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In severely pruned sandalwood plantations, the nutritional resources of defoliators are virtually removed, leaving few leaves, and hence the impact of feeding by a few species of moths shows a visible impact. Apart from the external damage caused by pruning, immense invisible internal damages are made, which make the tree species vulnerable to a small infestation of insects (Sundararaj et al 2018). The impact of pruning is masked by the infestation of insects, but in reality, the pruned, energy-starved trees are the rst to get affected by the insect infestations and fungal infections as they have lost the ability to resist (Laca 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In severely pruned sandalwood plantations, the nutritional resources of defoliators are virtually removed, leaving few leaves, and hence the impact of feeding by a few species of moths shows a visible impact. Apart from the external damage caused by pruning, immense invisible internal damages are made, which make the tree species vulnerable to a small infestation of insects (Sundararaj et al 2018). The impact of pruning is masked by the infestation of insects, but in reality, the pruned, energy-starved trees are the rst to get affected by the insect infestations and fungal infections as they have lost the ability to resist (Laca 2013).…”
Section: Resultsmentioning
confidence: 99%
“…group of insects with 67 species under 23 families, with the highest being the family Arctiidae with 9 species. SubsequentlySundararaj et al (2011) reported 159 insect species as phytophagous on sandalwood, of which Lepidoptera are the second most diverse group with 31 species representing 15 families. Moths display an immense mutual association with sandalwood by being nocturnal pollinators and, in return, getting food and shelter from sandalwood.…”
mentioning
confidence: 99%
“…Many earlier studies confirmed that the diversity and complexity of the vegetation positively affects the abundance of spiders (Sudhikumar et al 2005;Orguri et al 2014;Ossamy et al 2016). Sundararaj et al (2018) documented more species of insect pests and natural enemies from more diversified areas of sandalwood cultivation but with less severity of the infestations and not having requirement of the insecticidal application. Also, the plant diversity regulates insect herbivore populations by favouring the abundance and efficacy of associated natural enemies (Altieri & Letourneau 1984).…”
Section: J Ttmentioning
confidence: 99%
“…The scale insect (Chionaspis sp.) is one of the most destructive sandalwood pests, i.e., termites, stem borers, and defoliator [10][11][12][13]. This scale insect attacked on the seedlings in the sandalwood nursery at Timor reached 21% and increased to 100% within three months without any pest control treatments.…”
Section: Introductionmentioning
confidence: 99%